The Themes of Land and Fertility in the Book of Ruth - Sutskover, Talia (Journal for the study of the Old Testament, 2010)
A variety of words from the lexical fields of Land and Fertility occurs frequently at strategic points throughout the book of Ruth, often accompanied by special semantic and sound phenomena. This article focuses on the systematic accumulation of the lexical/ semantic patterns that bring Land and Fertility together as related theme markers. It is proposed that the theme underlined by elements of the lexical fields of Land and Fertility creates for Ruth, ancestress of King David, a set of new associations relating to the land of Beit-leḥem and giving birth to Obed (‭דבוע‬, connoting ‘tiller of the land’). These were intended to replace the negative associations attributed to Moabite aliens.